An evaluation of acute stroke ct protocol requests made in the emergency department. Issue 5 (8th May 2017) - Calma, Aicee; Gawarikar, Yash; Patel, Ronak
Abstract : Objectives: Multi-modal imaging, mainly non contrast CT brain (NCCT) with CT angiogram (CTA) with or without CT perfusion (CTP) is essential for the rapid evaluation of stroke patients, with the ultimate goal being accurate diagnosis and timely management of patients. 1 These imaging protocols are not always indicated, particularly for patients presenting outside the 4.5 hours thrombolysis window. The aim of the project was to look for disparity among ED physicians and neurologists for ordering of acute stroke protocol CT (NCCT with CTA) at our institute, for patients presenting outside the thrombolysis window. Methods: We conducted an audit of 131 patients from Calvary Public Hospital Bruce, ACT between April and October 2016. For each patient, we recorded the presenting symptoms, the indication for requesting an acute stroke protocol CT and their discharge diagnosis. Patients were divided into two groups; those who presented within and outside the thrombolysis window. Results: Seventy-seven of the 131 patients presented outside the thrombolysis window. ED physicians ordered significantly more CTAs compared with neurologists (OR 6.55, 95% CI 1.39 to 30.76, p=0.01). Furthermore, looking at stroke mimics there was a tendency to frequently request CTAs by ED physicians irrespective of whether the patients were within or outside the thrombolysis window (OR 5.7, 95% CI 0.84 to 38.82, p=0.07). Finally, when stratified for posterior circulation stroke symptoms; ED physicians were more likely to request CTA (OR 3.71, 95% CI 0.4593 to 29.93, p=0.21), mainly to rule out dissection or aneurysm. Conclusions: Our results suggest a greater need to educate ED physicians in recognising posterior circulation stroke symptoms and stroke mimics as well as thrombolysis guidelines. 2, 3 This will help avoid unnecessary ordering of CTAs particularly for patients presenting outside the thrombolysis window. This will avoid contrast related complications and also result in significant cost savings.